Clinical variants of lichen planus. (15th January 2013) - Wagner, Gunnar; Rose, Christian; Sachse, Michael Max
Summary Lichen planus is characterized by lichenoid, polygonal papules with fine white lines, called Wickham striae. Lesions most commonly occur on the limbs and on the dorsal aspect of the trunk. At the same time often leukoplakia of mucous membranes as well as nail disorders are seen. There are numerous variants of lichen planus which can be distinguished from the classical form on the basis of morphology and distribution of the lesions. The typical primary lesion of lichen planus may be replaced by other forms, such as patches, hyperkeratoses, ulcerations, or bullous lesions. Moreover, distribution patterns of these lesions may vary and include erythrodermic, inverse or linear arrangements. In contrast to these numerous clinical features, histologic findings remain characteristic in the variants, so that the diagnosis can be made securely. Differential diagnoses of lichen planus include diverse dermatoses such as bullous pemphigoid or paronychia.